2021
DOI: 10.1080/19475411.2021.1876176
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive model for epoxy shape memory polymer with regulable phase transition temperature

Abstract: The epoxy shape memory polymer (SMP) with adjustable phase transition temperature is a kind of high-performance shape memory polymer, which can change its phase transition temperature and improve its mechanical properties through the process of photo curing. An epoxy SMP constitutive model combining phase transition and viscoelasticity is established by discretizing the epoxy SMP into several glass phase units and rubbery phase units in this paper. The model includes the viscoelastic constitutive equations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…At the same time, its elastic modulus at 20°C is taken as the elastic modulus of the glassy phase. p and k are 0.9 and −0.2, respectively, reported in the literature (Zhao et al, 2021). Figure 4 shows the verification of the model through experiments.…”
Section: Design Of Smp Fixturementioning
confidence: 72%
See 1 more Smart Citation
“…At the same time, its elastic modulus at 20°C is taken as the elastic modulus of the glassy phase. p and k are 0.9 and −0.2, respectively, reported in the literature (Zhao et al, 2021). Figure 4 shows the verification of the model through experiments.…”
Section: Design Of Smp Fixturementioning
confidence: 72%
“…The constitutive model of SMP can provide a reference in the application design of SMP (Fan et al, 2020; Yarali et al, 2020). A constitutive model of epoxy SMP (Zhao et al, 2021), which parameters are easy to obtain and suitable for engineering applications, is employed to reference the distinctive design of SMP’s elastic modulus. It is assumed that the interior of SMP is composed of multiple glassy phase units and rubbery phase units, and the elastic modulus of SMP is described as…”
Section: Design Of Smp Fixturementioning
confidence: 99%
“…Due to being convenient to control the temperature, the heat-induced shape memory materials have attracted lots of interest. Lots of work has been performed on the design and fabrication of the heat-induced SMPs, and different types of heat-induced SMPs materials have been developed, including one-way [ 16 , 17 , 18 ], two-way [ 19 , 20 , 21 ], and multiple [ 21 , 22 ] SMPs materials.…”
Section: Introductionmentioning
confidence: 99%
“…The temporary shape can be maintained for a long time by cooling down below T trans and then the permanent shape can be automatically recovered upon reheating above T trans . Recently, SMPs and their composites have been applied in many fields including aerospace, biomedicine, textiles, and electron devices. So far, SMPs including polyurethane (PU), cyanate, , epoxy, polylactic acid, polyimide, , polyaryletherketone, and rubber , have been reported. However, the study of shape memory phenol-formaldehyde (SMPF) resin is rarely reported. , …”
Section: Introductionmentioning
confidence: 99%